Pengembangan Bahan Ajar Berbasis Modus Pendidikan Agama Islam Persepektif Imam Al-Ghozali Untuk Siswa Inklunsi - Herning Setiowati; Machunah Ani Zulfah (CENDEKIA, 2022)
This study aims to develop learning media for teaching materials in Islamic religious education learning materials and determine the feasibility of learning media for teaching materials. This research is development research (R&D) with a 4-D model. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Sammel which has 4 stages: define, design, develop, and disseminate. The feasibility of teaching materials and learning media is seen from the average validator assessment and student responses. The results of this study indicate that: (1) the method of developing this teaching material is to use 4-D stages. (2) The result of this research is that the development of this teaching material is suitable for use in learning. and analyze the efforts made by Herning Setiowati, Jombang, East Java in building a module-based teaching material, where the researcher tries to master the situation of the students to be studied. The method of collecting information was tried through observation, interviews, and documentation. Analysis of the information is tried through the stages of presenting information, information and drawing conclusions. The results of the study show that digital literacy was tried by Herning Setiowati, Jombang, East Java in making teaching materials.